2025 IMJ Reviewers (Internal Medicine Journal, 2026)
Workplace-related abuse, threats and assault are globally recognised as a significant risk for healthcare workers. This paper briefly reviews systemic factors contributing to aggression and violence before focussing on techniques first to identify high-risk patients and then sufficiently defuse their behaviour to enable a clinical assessment to be undertaken. General guidance is offered to enable compliance with relevant guardianship and mental health acts. Emphasis is placed on the importance of post-incident debriefing and, where necessary, counselling and for there to be systems in place to ensure supportive and efficient reporting. Training in the management of such patients should be included in both junior medical officer and specialty training programmes.